1785. Regional Variation of Antimicrobial Use in Japan From 2013 to 2016. (26th November 2018) - Kusama, Yoshiki; Ishikane, Masahiro; Tanaka, Chika; Kimura, Yuki; Yumura, Erina; Hayakawa, Kayoko; Ohmagari, Norio
Abstract: Background: Since antimicrobial resistance (AMR) is a global threat, judicious antimicrobial usage is required. Compared with European countries, antimicrobial use (AMU) is relatively low in Japan; however, the use of oral broad-spectrum antimicrobials is relatively high. Although the Japanese national action plan on AMR targets a 50% reduction in use of these oral broad-spectrum antimicrobials by 2020 from the level in 2013, regional variation in AMU in Japan is not well known. Methods: National antimicrobial sales data from 2013 to 2016 was obtained from IQVIA Japan (Tokyo, Japan), which captures 99% of total sales in Japan. Antimicrobials were classified by the World Health Organization (WHO) defined Anatomical Therapeutic Chemicals (ATC) classification. WHO measures the number of antimicrobial use by Defined Daily Dose per 1, 000 inhabitant-days (DID). From 2013 to 2016, the difference in DID amongst each prefecture was analyzed, and comparison amongst the three major regions of East, Central, and West Japan was performed using Mann–Whitney U test. Results: From 2013 to 2016, the median (max, min) AMU (DID) change was −0.4 (2.8, −1.6). During the study period, 34 prefectures showed increasing trends and 13 prefectures showed decreasing trends. Median (max, min) AMU (DID) for total antimicrobials, oral cephalosporins, macrolides, and quinolones in 2016 was 14.4 (18.7, 11.2), 3.5 (6.9, 2.5), 4.5 (6.3, 3.2), and 2.8 (3.7, 1.9), respectively. The median total AMU (DID) in East, Central, and West Japan in 2016 was 13.2, 14.4, and 15.8, respectively. Median oral cephalosporins AMU (DID) in Central Japan (3.69) was significantly higher than that in East Japan (3.33) ( P = 0.025). Median oral macrolides AMU (DID) in East Japan (4.11) was significantly smaller than that in Central (4.61) and West Japan (4.70) ( P < 0.01). Median oral quinolones AMU (DID) in West Japan (3.28) was significantly higher than that in East (2.29) and Central Japan (2.73) ( P < 0.01) (figure). Conclusion: From 2013 to 2016, significant regional variations of oral AMU were observed in Japan. Further studies are needed to specify the appropriate targets of antimicrobial stewardship intervention to reduce oral broad-spectrum AMU in Japan. Disclosures: All authors: No reported disclosures.